Structure and sedimentation characterisation of sheared Mg(OH)2 suspensions flocculated with anionic polymers. (15th February 2021) - Lockwood, Alexander P.G.; Peakall, Jeffrey; Warren, Nicholas J.; Randall, Geoff; Barnes, Martyn; Harbottle, David; Hunter, Timothy N.
Graphical abstract: Highlights: Effectiveness of anionic polymers on the flocculation of Mg(OH)2 was established. Largest ( d90 ) sized flocs were more influential on the zonal settling rate. A Fractal Modified Richardson-Zaki predictive settling rate model was examined. Model provided a close first order zonal settling rate prediction, using d90 sizes. A full model sensitivity analysis highlighted fractal dimension sensitivity. Abstract: In this study, magnesium hydroxide (Mg(OH)2 ) suspensions were flocculated using two polyacrylamide-poly(acrylic acid) copolymers with charge densities of 30% or 40%. Structural characteristics, including particle size distribution, shape and fractal dimension of the resultant flocs were investigated using complementary techniques; static light scattering, focused beam reflectance measurement, automated optical microscopy and cryogenic scanning electron microscopy. Sedimentation rates were analysed for 2.5 vol.% dispersions at various polymer concentrations and compared to predictions from a fractal modified Richardson-Zaki (FMRZ) settling model. FMRZ model predictions using the 90 th percentile ( d90 ) floc sizes produced the most accurate correlations to experimental settling data, as these larger flocs likely dominate settling dynamics by 'netting' smaller particles. Overall, the FMRZ settling model provided a first approximation of zonal settling rates, but when further examined by multivariate analysis, was found to be critically sensitive to small changes in fractal dimension.